Efeitos antrópicos sobre a qualidade dos sedimentos do rio Toledo (PR, Brasil): análises físico-químicas e ecotoxicológicas - Soares, Juliane Alessandra Cavalieri (2017)
The sediments present capacity of accumulation and retention of several contaminants and for this reason, the evaluation of this compartment is extremely important. Therefore, this study had as objective to evaluate the quality of the sediments of the Toledo river (PR) through physical chemical and ecotoxicological analyzes. The samplings were carried out bimonthly between July/2015 and May/2016 in five sites, from the river source to the river mouth. Were realized particle size analyses, concentrations of trace elements (Cu, Zn, Cd, Pb, Cr, Mn, Fe and Al) in the sediments, concentrations of nutrients (phosphorus and nitrogenous forms) in elutriates prepared according to NBR 12713: 2004; and toxicity tests with elutriates using D. magna as test organism. The highest mean concentrations of trace elements were observed at sites P1, P2 and P3 (areas of agricultural influence), with Cu and Cd exceeding the limits Tel (Less likely to have adverse effects on aquatic biota). Already the nutrients were observed in higher concentrations in the P4 sites (area susceptible to discharges of industrial and domestic effluents) and P5 (rural/urbana area). In relation to the toxicity tests, the results indicated risks to the aquatic biota since although organisms can survive when exposed, end up having biological functions (such as reproduction), committed. Concluding, the study evidenced the influence of anthropic pressures in all the sites sampled (both urban and rural areas), revealing inadequate conditions to the survival of organisms.